Glutamine Synthetase Induction in Embryonic Neural Retina: Immunochemical Identification of Polysomes Involved in Enzyme Synthesis - Sarkar, P. K. (1973)
Glutamine synthetase (EC 6.3.1.2) in embryonic neural retina in culture is rapidly induced by hydrocortisone. Retina polysomes involved in translation of this enzyme were precipitated with a high degree of specificity by the gammaglobulin isolated from antiserum against the enzyme (anti-enzyme gammaglobulin). Using immunoprecipitation procedures, we determined that the amount of polysome-bound nascent enzyme was maximal in polysomes comprising 9-14 ribosomes and was about 3-fold higher in the induced than in the noninduced retina. Within this size group of polysomes, those comprising 11-13 ribosomes showed consistently greater binding of anti-enzyme [(125)I]gammaglobulin than of normal [(125)I]-gammaglobulin. This size of polysomes corresponds to that calculated for a monocistronic messenger RNA for the subunit of this enzyme, which has a molecular weight of 42,000. The application of immunochemical techniques to identification of templates for synthesis of an enzyme in embryonic cells that constitutes less than 1% of the total cellular proteins indicates the usefulness of this method for detailed studies on regulation of other quantitatively minor products significant in cell differentiation.